Policy perception, job satisfaction and intentions to remain in rural area: evidence from the National Compulsory Service Programme in China - Yanrong He; Peicheng Wang; Yanrong Du; Hange Li; Yanhua Chen; Jiming Zhu (BMC, 2024)
Abstract Background Exploring factors that may influence general practitioners (GPs)' intentions to remain in rural area is necessary to inform the training and placement of future medical workforce in rural area. However, little is known about how GPs' perception towards the National Compulsory Service Programme (NCSP) and job satisfaction impact their turnover intention. This paper explores GPs' intentions to remain in rural China and how their policy perception and job satisfaction predict the intentions. Methods We conducted a cross-sectional, online survey from December 2021 to February 2022 to investigate GPs' perception towards NCSP, job satisfaction, and intentions to remain in rural area. Eligible participants were GPs who were required to provide health services as part of NCSP at township health centres of 9 provinces which could represent all NCSP GPs in China. Multinomial logistic regression analyses were performed to explore the associations between policy perceptions, job satisfaction, and intentions to remain. Results Of 3615 GPs included in the analysis, 442 (12.2%) would like to remain in rural area and 1266 (35.0%) were unsure. Results of the multinomial logistic regression analyses showed that compared with GPs who would leave, GPs with higher perception scores for the restriction on taking postgraduate exam (RRR: 1.93, 95% CI 1.72, 2.16) and the commitment to work for six years (RRR: 1.53, 95% CI 1.31, 1.78) were more likely to remain. In contrast, GPs who had higher perception scores for completing standardised residency training (RRR: 0.75, 95% CI 0.64, 0.88) and passing National Medical Licensing Examinations (RRR: 0.74, 95% CI 0.62, 0.87) were more likely to leave. GPs who were satisfied with the freedom of choosing work methods (RRR: 1.52, 95% CI 1.25, 1.84) and chances of promotion (RRR: 1.60, 95% CI 1.32, 1.94) were more likely to remain. Conclusions This study highlights the significance of policy perception and job satisfaction on GPs' intentions to remain in rural area. Factors such as career advancement and the empowerment of GPs to build on and use their skills and abilities should be taken into account when designing rural placement programmes.